2022
DOI: 10.1002/adma.202206385
|View full text |Cite|
|
Sign up to set email alerts
|

3D‐Bioprinted Phantom with Human Skin Phototypes for Biomedical Optics

Abstract: Skin consists of a lamellar structure with diverse cell types (e.g., immune cells, melanocytes, and basal cells) that periodically detach from the basement membrane, move to the surface, and die for self-renewal. [3] Melanocytes are a critical cell type that generate melanin to absorb UV light (290-400 nm), which is a major risk for skin diseases (e.g., melanoma) due to DNA damage. [4][5][6][7] Here, melanin-containing organelles called melanosomes are transferred to the surrounding keratinocytes. This increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…This correlation is attributed to the energy dissipation via nonradiative decay (or heat) following light absorption. 46 The decrease in the quantum yield (QY) from 0.16 for the free dye to 0.05 also supports the observed PL quenching (Table S2). Our group has reported near-complete self-quenching of the dye PL and enhanced PA signal through aggregation-associated interactions, realized by bringing a dye dimer in close proximity using a short linker.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This correlation is attributed to the energy dissipation via nonradiative decay (or heat) following light absorption. 46 The decrease in the quantum yield (QY) from 0.16 for the free dye to 0.05 also supports the observed PL quenching (Table S2). Our group has reported near-complete self-quenching of the dye PL and enhanced PA signal through aggregation-associated interactions, realized by bringing a dye dimer in close proximity using a short linker.…”
Section: Resultssupporting
confidence: 72%
“…In Figure c, the coacervates show a 2- to 4-fold PA enhancement over the disassembled samples across three tested dye concentrations. This correlation is attributed to the energy dissipation via nonradiative decay (or heat) following light absorption . The decrease in the quantum yield (QY) from 0.16 for the free dye to 0.05 also supports the observed PL quenching (Table S2).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…To induce reversible aggregation of the AuNPs, we used positively charged Arg- and Lys-based peptide residues (i.e., RRK). The RRK peptide could induce plasmonic coupling by electrostatic attractions between negatively charged citrate molecules and guanidine and amine groups in RRK (Figure a). , The size of AuNPs increased upon addition of RRK peptides, as confirmed by transmission electron microscopy (TEM) and dynamic light scattering (DLS) (Figures b and S1). UV–vis spectroscopy showed that the plasmonic resonance peak (520 nm) of AuNPs redshifted to 648 nm; visually, the sample changed color from red to blue (Figure c).…”
Section: Resultsmentioning
confidence: 77%
“…[14][15][16][17] Nevertheless, although most reported phantom materials boast stability advantages, [18][19][20] they exhibit poor repeatability and limited CT similarity to human tissue. 16,21 These materials lack adequate CT control performance, as their single X-ray attenuation characteristics can only absorb fixed Xray energy. Consequently, researchers are actively seeking an exceptional function phantom that combines feature stability, repeatability, CT similarity, and repeatable texture.…”
Section: Introductionmentioning
confidence: 99%